1972
DOI: 10.1063/1.1654074
|View full text |Cite
|
Sign up to set email alerts
|

Passive Mode Locking of Flashlamp-Pumped Dye Lasers Tunable between 580 and 700 nm

Abstract: Employing polymethine dyes as saturable absorbers and intracavity Fabry-Perot interferometers, a flashlamp-pumped cresyl-violet dye laser has been mode locked to produce picosecond pulses (3–5 psec) frequency tunable from 644 to 704 nm. The frequency tuning ranges of mode-locked rhodamine 6G and rhodamine B dye lasers have also been extended to cover 584 to 645 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

1973
1973
1988
1988

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(26 citation statements)
references
References 10 publications
0
25
0
1
Order By: Relevance
“…The frequency range covered was later extended [9] over the spectral region 580 to 700 nm with three lasing dyes Rhodamine 6G, Rhodamine B and cresyl-violet with one of the polymethine dyes, DODCI, DQTCI, DTDCI or DDCI employed as the saturable absorber for the appropriate lasing dye. To obtain the shortest duration pulses it was necessary to select both the laser mirrors and the coatings of the tuning etalons to have the optimum reflectivities at the required lasing wavelengths.…”
Section: Ilmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency range covered was later extended [9] over the spectral region 580 to 700 nm with three lasing dyes Rhodamine 6G, Rhodamine B and cresyl-violet with one of the polymethine dyes, DODCI, DQTCI, DTDCI or DDCI employed as the saturable absorber for the appropriate lasing dye. To obtain the shortest duration pulses it was necessary to select both the laser mirrors and the coatings of the tuning etalons to have the optimum reflectivities at the required lasing wavelengths.…”
Section: Ilmentioning
confidence: 99%
“…The introduction of interferometric tuning [8] permitted the generation of pulses of transform-limited duration, frequency tunable from 580 to 700 nm [9], by employing rhodamine and cresyl-violet dyes with the appropriate polymethine saturable absorbers. About the same time the development of the 'Photochron' picosecond streak-camera [10][11][12] permitted direct linear measurements of pulse durations.…”
Section: Introductionmentioning
confidence: 99%
“…The flashlamp-pumped organic dye laser oscillators generate intense, frequency tunable, light pulses of several picoseconds duration and several tens of megawatt power [22,208,210,211]. Using different lasing dyes and saturable absorbers passive mode-locking has been achieved in the wavelength region between 450 and 840 nm.…”
Section: Passive Mode-locking With Saturable Absorbersmentioning
confidence: 99%
“…A similar result has been reported for a Nd:YAG mode-locked [14] láser. The discrepancy can be explained for the mode-locked pulse train in terms of spectral broadening due to selfphase modulation when the láser is puinped well above the threshold [6].…”
mentioning
confidence: 99%
“…Phase-conjugation reflection with lower efficiency, has also been measured [3] in an intra-cavity saturable absorber dye cell in the experimental arrangement conunonly used for passive mode-locking of pulsed and CW dye lasers [4,5], Photoisomer effeets [6] in the saturable absorber dye were found [3] to be important in the phase-conjugation process, particularly when the láser was tuned to longer wavelengths. Martin and Hellwarth [7] have shown that thermally induced refractive Índex changes [8][9][10][11] were the dominant mechanism in a variety of liquids employed in a four-wave mixing process for image conversión from infrared to visible and more recently the influence of the thermal grating in phase conjugation was discussed by Heilweil et al [12].…”
mentioning
confidence: 99%